2007
DOI: 10.1038/sj.ki.5002154
|View full text |Cite
|
Sign up to set email alerts
|

The janus face of immunosuppression – de novo malignancy after renal transplantation: the experience of the Transplantation Center Munich

Abstract: After decades of successful organ transplantation clinicians continue to be troubled by the increasing incidence of cancers under maintenance immunosuppression. In this study, we examined rates of malignancies in 2419 renal transplant recipients transplanted in our institution between 1978 and 2005. In renal transplant recipients the cumulative incidence of cancer after 25 years was 49.3% for all tumors and 39.7% excluding non-melanoma skin cancers, compared with 21% for a normal sex- and age-matched populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
136
3
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 19 publications
15
136
3
5
Order By: Relevance
“…[33][34][35][36]43,44 In this study, we showed that CXCR3 and its ligands are overexpressed in human renal cancer, one of the major cancers after solid organ transplantation. 18,45 The two splice variants of CXCR3 mediate distinctly different signals and have completely opposite functions in tumor cells as well as in a variety of normal cell types, such as lymphocytes, endothelial cells, and airway epithelial cells 28,37,39,40 ; CXCR3-A promotes chemotaxis and cell proliferation, whereas CXCR3-B mediates growth inhibition. 28,37,40 Thus, it is likely that signaling through CXCR3-B in renal cancer cells may inhibit cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36]43,44 In this study, we showed that CXCR3 and its ligands are overexpressed in human renal cancer, one of the major cancers after solid organ transplantation. 18,45 The two splice variants of CXCR3 mediate distinctly different signals and have completely opposite functions in tumor cells as well as in a variety of normal cell types, such as lymphocytes, endothelial cells, and airway epithelial cells 28,37,39,40 ; CXCR3-A promotes chemotaxis and cell proliferation, whereas CXCR3-B mediates growth inhibition. 28,37,40 Thus, it is likely that signaling through CXCR3-B in renal cancer cells may inhibit cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…drugs are responsible for the increased skin cancer risk (16) or to determine the general mechanisms underlying the increased risk (16,60,61). Most transplant recipients are adults when they receive their new organs, and have accumulated years of sunlight-related skin damage.…”
Section: Duncan Et Almentioning
confidence: 99%
“…case, the patient received a long-term immunosuppressive regimen including mycophenolate and tacrolimus, both of which are associated with a higher risk of developing PTLD [15]. EBV infection is a key contributor to the development of PTLD.…”
Section: A B C D E Fmentioning
confidence: 99%